Electrospun hydrogel fibers guide HKUST-1 assembly. (December 2022) - Fox, David W.; Antony, Dennis-Xavier; Sip, Yuen Yee Li; Fnu, Joshua; Rahmani, Azina; Jurca, Titel; Zhai, Lei
Abstract: Metal organic frameworks (MOFs) have been touted for their large surface areas, with interconnected porosity throughout their crystal framework. Designing MOFs with controlled structure and size and with stable attachment to surfaces are two objectives to enhance practical utilization of MOFs for their many applications. We propose that tuning the composition of electrospun hydrogel nanofibers makes them excellent substrates to promote growth of MOFs (i.e. Cu-based HKUST-1) with controlled size. Hydrogel fiber mats composed of poly(acrylic acid) (PAA) and poly(allylamine hydrochloride) (PAH) were produced through electrospinning PAA/PAH solutions followed by a thermal crosslinking. The hydrogel fiber mats were immersed in copper acetate aqueous solutions to uptake copper ions. Upon the immersion of the hydrogel fibers mats with copper ions in a separate linker solution, the released copper ions reacted with linkers, allowing for a controlled assembly of MOF structures on the hydrogel fibers. An increased PAA component in the PAA/PAH hydrogel fibers increased metal ion uptake through the interactions between the carboxylic groups and metal ions. Upon the release of metal ions in the linker solution, MOF crystals of a smaller scale and denser coverage than fibers with a lower proportion of PAA were observed. A similar trend was observed in fibers of varying diameter, with variations in crystal growth attributed to the metal ion flux at the fiber-solution interface. The crystals appeared well-separated and densely coated across the fibers and could undergo rapid partial activation in dry environments. Graphical Abstract: ga1